Penerapan Model Pembelajaran Picture and Picture untuk Meningkatkan Kemampuan Menulis Narasi Siswa - Wijayanti, Dwi Retno; Hadi, Panji Kuncoro; Soleh, Dwi Rohman (Universitas PGRI Madiun, 2024)
This research aims to determine the increase in students' narrative writing abilities and learning activeness of class IV students at SDN Watualang 1, Ngawi District, Ngawi Regency after implementing the picture and picture learning model. This research uses Classroom Action Research with data collected through test techniques, non-test techniques, observation, interviews and documentation. The research subjects were 20 people, analyzed using data collection, data reduction, data presentation and drawing conclusions or verification. The results of the research showed that there was an increase in the narrative writing ability of class IV students at SDN Watualang 1, Ngawi District, Ngawi Regency after implementing the picture and picture learning model. This can be seen from the increase in the percentage of learning completion in narrative writing skills from cycle I of 80% with an average class score of 73.75 to 100% in cycle II with an average class score of 79.75. There was an increase in the learning activity of class IV students at SDN Watualang 1, Ngawi District, Ngawi Regency after implementing the picture and picture learning model. This can be seen from the increase in the percentage of complete learning activities from cycle I of 80% to 100% in cycle II.